Genetic analyses of processing involving C-terminal cleavage in penicillin-binding protein 3 of Escherichia coli. - Hara, H (1989)
The processing of Escherichia coli penicillin-binding protein 3 (PBP 3) was investigated by gene manipulation for producing hybrid and truncated PBP 3 molecules. The hybrid PBP 3 was processed when the N-terminal 40 residues of PBP 3 were replaced by the murein lipoprotein signal peptide which lacked the cysteine residue for processing and followed by seven extra linker residues. In contrast, the PBP 3 molecules truncated at Thr-560 (28-residue deletion) or at Thr-497 (91-residue deletion) were not processed, and those truncated at Phe-576 (12-residue deletion) were processed at a greatly reduced rate. The results indicate that the C-terminal part, rather than the N-terminal part, is involved in the processing. This was supported by the result that the purified mature PBP 3 retained the complete N-terminal sequence with Met for translation initiation. The cleavage at the C-terminal region was shown by the loss of [35S]cysteine label when the cysteine-free hybrid PBP 3 joined to a cysteine-rich extra peptide tail was processed into the mature form. Confirmative assays for processing of PBP 3 were aided by a newly found prc mutant, defective in the processing involving the C-terminal region. A plasmid that directs PBP 3 truncated at Thr-560 complemented a thermosensitive PBP 3 mutation, but the truncated product was unstable in vivo. This suggests the importance of C-terminal hydrophobic regions that terminate at Leu-558 to PBP 3 functioning and the requirement of further-distal peptides for the stability of PBP 3.